Evaluating the Impact of Remote-Mentoring Programs on Prospective Teacher Preparedness and Self-Efficacy During Initial Teacher Training - Yusuf Hidayat; Ani Herniawati; Rohit Rastogi (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study evaluates the impact of remote-mentoring programs on prospective teacher preparedness and self-efficacy during their initial teacher training. Teacher preparation is a critical element in developing effective educators, and mentoring plays a pivotal role in enhancing the professional development and confidence of novice teachers. With the growing trend of remote learning, particularly due to the COVID-19 pandemic, remote mentoring has emerged as an alternative to traditional face-to-face mentoring. The objective of this study was to assess how remote mentoring influences prospective teachers’ readiness to teach and their belief in their teaching abilities. Through a quasi-experimental design, the study compares two groups of prospective teachers: one group receiving remote mentoring and another group without it. The data were collected using self-efficacy questionnaires and in-depth interviews, focusing on participants' perceived teaching readiness, confidence, and experiences with remote mentoring. The findings suggest that remote mentoring significantly enhanced teaching self-efficacy and preparedness compared to the non-mentored group. While remote mentoring provided flexibility and accessibility, challenges such as technological barriers and the lack of personal interaction were identified. The study concludes that remote mentoring can be an effective tool for teacher preparation, particularly in areas where traditional mentoring is difficult to implement. Recommendations include the use of blended approaches, combining online mentoring with occasional face-to-face interactions, to overcome the limitations of remote learning. Further research is suggested to explore the long-term effects of remote mentoring on teacher performance and to compare mentoring practices across different disciplines and regions.